Detection of Significant Aprotic Solvent Effects on the Conformational Distribution of Methyl 4‐Nitrophenyl Sulfoxide: From Gas‐Phase Rotational to Liquid‐Crystal NMR Spectroscopy. Issue 11 (23rd June 2015) - Celebre, Giorgio; De Luca, Giuseppina; Di Pietro, Maria Enrica; Giuliano, Barbara Michela; Melandri, Sonia; Cinacchi, Giorgio
Abstract The conformational equilibrium of methyl 4‐nitrophenyl sulfoxide (MNPSO) was experimentally investigated in the gas phase by using microwave spectroscopy and in isotropic and nematic liquid‐crystal solutions, in which the solvents are nonaqueous and aprotic, by using NMR spectroscopy; moreover, it was theoretically studied in vacuo and in solution at different levels of theory. The overall set of results indicates a significant dependence of the solute conformational distribution on the solvent dielectric permittivity constant: when dissolved in low‐polarity media, the most stable conformation of MNPSO proved to be strongly twisted with respect to that in more polar solvents, in which the conformational distribution maximum essentially coincides with that obtained in the gas phase. We discuss a possible explanation of this behavior, which rests on electrostatic solute–solvent interactions and is supported by calculations of the solute electric dipole moment as a function of the torsional angle. This function shows that the least polar conformation of MNPSO is located at a twist angle close to that of the conformational distribution maximum found in less‐polar solvents. This fact, associated with a relatively flat torsional potential, can justify the stabilization of the twisted conformation by the less‐polar solvents.